(untitled) (Phenomenology, Humanities and Sciences, 2025)
This paper explores the relationship between reflection, attention, and the practice of phenomenology, grounding its analysis in both the structures of consciousness and the methodological demands of phenomenological research. The first section examines reflectivity as both an essential structure of consciousness and a methodological tool, distinguishing between reflective and pre-reflective modes of awareness and addressing the interplay between receptivity and spontaneity within reflective acts. The second section elaborates on the temporal dynamics of reflection, emphasizing its retrospectivity and retroactivity as key to understanding how experience is shaped and revisited through reflective acts. The third section investigates the interrelation of attention, reflection, and experience, positing attention as a fundamental mediator in the reflective engagement with lived phenomena. Finally, the paper argues for the centrality of attention in phenomenological practice, conceptualizing it as a methodological foundation for understanding the nuances of lived experience